HUBUNGAN PENGETAHUAN DAN PHBS (PERILAKU HIDUP BERSIH DAN SEHAT) TERHADAP KEJADIAN ISPA DI DESA ATU LINTANG - Sri Rahayu; Lia Muslima; Nurlaely HS (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACT Clean and Healthy Living Behavior is an absolute necessity. Implementation of Clean and Healthy Living Behavior that is lacking will facilitate the emergence of diseases, especially ARI (acute respiratory tract infection) which is one of the main causes of morbidity and mortality of infectious diseases in the world. This study aims to determine the relationship between knowledge and PHBS (clean and healthy living behavior) to the incidence of ARI in Atu Lintang. This study uses a quantitative research method with an analytical research design and a cross-sectional approach. This research was conducted on September 3-16, 2024. This research was conducted in Atu Lintang Village, Atu Lintang District, Central Aceh Regency. The population in this study was 352 family cards, while the number of samples was 78 respondents using random sampling techniques. Data collection using a questionnaire by interview, data was analyzed univariately and bivariately with the chi-square statistical test. The results of the study obtained 42 (53.8%) respondents with less knowledge category and there were 46 (59.0%) respondents with negative PHBS category, followed by 47 (60.3%) ISPA incidence results. The results of the Knowledge chi-square test analysis showed a p value = 0.000 <0.05, and PHBS showed a p value = 0.007 <0.05, this indicates that there is a relationship between Knowledge and PHBS on ISPA incidence in Atu Lintang village. It is hoped that this study can be used as motivation and change in the community about how to prevent if family, friends, relatives get ISPA. Keywords : Knowledge, CHLB (Clean and Healthy Living Behavior), ARI (Acute Respiratory Infections) incident